PENGARUH ONLINE FLOW ELEMENTS DAN KEPUASAN PADA PENGALAMAN BELANJA HEDONIS DAN UTILITARIAN: STUDI KASUS PADA SOCIAL COMMERCE - Hidayati, Lukluk Atul; Purwantini, Anissa Hakim (Optimum: Jurnal Ekonomi dan Pembangunan, 2017)
This study examined the relationship between online flow elements on hedonic and utilitarian online shopping experience and its influence on the satisfaction that later influenced the social commerce intention. The research sample using purposive sampling method of social media users who ever search information and purchase online through social media as Facebook, Instagram, Twitter or Path. The results of this study indicate that arousal, challenge and time distortion have positive effect on hedonic online shopping experience, whereas telepresence havenât significant effect. Importance, interactivity and skill positively influence utilitarian online shopping experience, while the control has no effect. Utilitarian shopping experience influence satisfaction, whereas no significant effect on hedonic shopping experience. Satisfaction positively influence repurchase intention in social commerce.